2023
DOI: 10.3390/ijms24032924
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency: An Underestimated Factor in Sepsis?

Abstract: Vitamin D is an important immune modulator that is linked to infection susceptibility. It has been suggested that vitamin D deficiency plays a role in sepsis and septic shock because vitamin-D-related pathways are associated with various immunological, endocrine, and endothelial functions. Previous research has yielded inconclusive results regarding the link between mortality and vitamin D deficiency in sepsis patients. In patients with sepsis and severe vitamin D deficiency, an adequate vitamin D concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…[34] Sepsis, as a systemic inflammatory response syndrome, is closely related to vitamin D. The multiple functions of vitamin D in the immune system 's response to infection may make it an important part of the fight against sepsis. [31] The cause of sepsis is systemic organ dysfunction caused by the imbalance of immune response after the host is infected by pathogens, mainly manifested as enhanced systemic inflammatory response. [34,35] Immune dysfunction, mitochondrial dysfunction, coagulation issues, neuroendocrine-immune network issues, endoplasmic reticulum stress, and autophagy are all factors in the pathophysiology of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Sepsis, as a systemic inflammatory response syndrome, is closely related to vitamin D. The multiple functions of vitamin D in the immune system 's response to infection may make it an important part of the fight against sepsis. [31] The cause of sepsis is systemic organ dysfunction caused by the imbalance of immune response after the host is infected by pathogens, mainly manifested as enhanced systemic inflammatory response. [34,35] Immune dysfunction, mitochondrial dysfunction, coagulation issues, neuroendocrine-immune network issues, endoplasmic reticulum stress, and autophagy are all factors in the pathophysiology of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…A large and growing body of evidence supports a role for vitamin D in inflammation and modulation of immune function, and vitamin D deficiency has been associated with increased systemic levels of inflammatory markers such as interleukin‐6 (IL‐6) 108,109 . Vitamin D has been shown to inhibit production of numerous proinflammatory cytokines and increase production of anti‐inflammatory mediators in cells expressing the VDR, including many different immune cell populations 110 . Preclinical studies have demonstrated that vitamin D administration can reduce the occurrence or slow the progression of many different immune‐related diseases 73,111 .…”
Section: Keloids: More Than Just ‘Scars’mentioning
confidence: 99%
“…108,109 Vitamin D has been shown to inhibit production of numerous proinflammatory cytokines and increase production of anti-inflammatory mediators in cells expressing the VDR, including many different immune cell populations. 110 Preclinical studies have demonstrated that vitamin D administration can reduce the occurrence or slow the progression of many different immune-related diseases. 73,111 This is consistent with epidemiological evidence of associations between vitamin D deficiency and immune-related diseases and disorders, including type 1 diabetes, multiple sclerosis, psoriasis, rosacea, rheumatoid arthritis, respiratory infections, cardiovascular disease, systemic lupus erythematosus, inflammatory bowel disease and sepsis, in addition to keloid disorder.…”
Section: Vitamin D and Keloid Disorder: Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Vitamin D in immune function is well reported with a growing evidence base linking low levels to poorer outcomes from infectious diseases [ 1 3 ]. Further, Vitamin D is vital for calcium homeostasis and skeletal health, with risk of rickets, osteomalacia and osteopaenia in insufficient or deficient states [ 4 ].…”
Section: Introductionmentioning
confidence: 99%